A man for all markets : from Las Vegas to Wall Street, how I beat the dealer and the market - Thorp, Edward O. (Random House, 2017)
Traces the author's experiences as a mathematics wizard, author, inventor, hedge-fund manager, and card-counter who revealed casino-beating strategies, invented the first wearable computer, and launched a Wall Street revolution.